Categorização de formas de lagos amazônicos a partir de imagens CBERS - Silva Júnior, Gilberto Pedro da (2012)
In this thesis we propose a technique of image analysis in order to categorize lakes of the Amazon River basin. The images studied are generated by the sensor CBERS, and the procedure is to extract edges, in order to get features from these edges and classify them into one of a known number of classes. The classification process is made by maximum likelihood Gaussian classifier, and the best features in terms of expressiveness and computational cost are identified by an exhaustive search.